The THE INFLUENCE OF BRAIN GYMNASTIC TO LEARNING ACHIEVEMENT ON STUDENTS IN MOJOKERTO REGENCY - Tri Ratna Ningsih; SITI INDATUL LAILI; Tri Peni (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
Memory is used for building self-reliance and self-confidence in children. Memory disorders will complicate learning process and cause health problems for children. Exercise activities will familiarize children to maintain the main cognitive function of the brain and can help them to achieve achievement. This study aims to determine the influence of brain gymnastic to learning achievement on Al-Akbar Islamic Elementary School students Mojokerto. This research was done with quasi-experiment method with